2021
DOI: 10.1098/rsif.2021.0158
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying community resilience based on fluctuations in visits to points-of-interest derived from digital trace data

Abstract: This research establishes a methodological framework for quantifying community resilience based on fluctuations in a population's activity during a natural disaster. Visits to points-of-interests (POIs) over time serve as a proxy for activities to capture the combined effects of perturbations in lifestyles, the built environment and the status of business. This study used digital trace data related to unique visits to POIs in the Houston metropolitan area during Hurricane Harvey in 2017. Resilience metrics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…Several methods have been proposed to evaluate the community impact of crisis events using new technology that provides large-scale digital trace data. (10,18) Detailed spatiotemporal data offer unique insights into the interdependence of disaster problems, human activity, and urban mobility. The new insights can help us assess the impact of disaster more accurately (19), respond to disaster promptly (20), and enhance preparedness for future events (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been proposed to evaluate the community impact of crisis events using new technology that provides large-scale digital trace data. (10,18) Detailed spatiotemporal data offer unique insights into the interdependence of disaster problems, human activity, and urban mobility. The new insights can help us assess the impact of disaster more accurately (19), respond to disaster promptly (20), and enhance preparedness for future events (21).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of visits to POIs, such as restaurants, gas stations, and grocery stores, reveals insights into how people move around a city and where people visit during a disaster event. Several studies have been conducted to assess the impact or determine the signal of disasters, such as the COVID-19 pandemic (20,28), Hurricane Harvey (18), and Hurricane Irma (29), by implementing the visit data of POIs. The fluctuations in POI visits could provide reliable insights regarding disrupted access to critical facilities, such as grocery stores and restaurants.…”
Section: Introductionmentioning
confidence: 99%
“…These community-scale big datasets have become more commonly available on the same day and at fine spatial resolution affording capture of human activities, such as daily activity indexes, transaction activities, online communications, and mobility. Large-scale flood-caused perturbations cause disruptions at the smaller scale of human activities (Podesta et al 2021). Hence, variations in human activities in a flood-affected community signal impacts on the community (Farahmand et al 2021), which can be further used for the rapid assessment of flood impacts (e.g., Fan et al 2020;Yuan et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations in the density of population activities (obtained through aggregate cell phone signals) or Waze road flooding reports could indicate local flood inundation status in an area outside a floodplain (Farahmand et al 2021;Praharaj et al 2021). Podesta et al (2021) compared the fluctuations in visits to points of interest (POIs) during normal periods to the Hurricane Harvey period and found that such fluctuations can be used to assess flood impacts. Yuan et al (2021b) assessed the flood impacts of Hurricane Harvey through the analysis of variations in credit card transactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation